A prospective study of feasibility and short term outcome of stoma reversal under local anaesthesia - Kumar, Ashok; Kumar, Yogesh; Singh, Vineet; Kumar, Arvind (International Surgery Journal, 2017)
Background: Stoma fashioning (ileostomy and colostomy) are very important and established procedures for deviation of bowel contents to procure the distal anostomosis. It is a very common procedure in cases of bowel obstruction, perforation, inflammatory bowel disease and large bowel disorders like Ca colon and Ca rectum, colonic fistulas, trauma to colon and rectum. Stoma reversal is a routine procedure but is usually performed using general or regional anaesthesia but large number of patient list for stoma reversal under general or regional anaesthesia, led to unnecessary delay in stoma reversal due to paucity of anaesthesia. Local anaesthesia has thus proved useful to handle a large load of stoma reversal, so we investigated feasibility of performing stoma reversal using local anaesthetic agent. Methods: Total 54 patients underwent for stoma reversal under local anaesthesia, admitted to Department of General Surgery, Nehru Hospital, B. R. D. Medical College, Gorakhpur, Uttar Pradesh, India. Results: Reversal of stoma could be comfortably done under safe dose of local anaesthesia, most of the patients remain comfortable intraoperatively, 4 out of 54 patients had systemic complications like vomiting and bradycardia and 2 had associated bowel injury. only 2 patients had minor anostomotic leak and 1 had developed fecal fistula while rest had normal intact anostomosis. Only 2 patients had reported moderate pain and 1 had mild pain according to visual analog scale and in 42 out of 54 patients had normal wound healing while 5 had minor erythema, 6 had seroma formation and 1 had complain of pus discharge. Conclusions: Reversal of STOMA can be performed safely and comfortably under local anaesthesia. Post op short term outcome and complications are comparable to that done under general or regional anaesthesia.